Analisis Peran dan Hambatan Dewan Perwakilan Rakyat Daerah (DPRD) Terhadap Persetujuan Kerjasama Luar Negeri (Paradiplomasi) di Sumatera Utara - Muhammad Novan Prasetya (Frequency of International Relations (FETRIAN), 2021)
Paradiplomacy is a term for the science of international relations which refers to foreign cooperation carried out by local governments in order to develop their regions independently, not only waiting for instructions from the central government, but still in accordance with applicable regulations, paradiplomacy within the national legal framework is stated in the Constitution Number 37 of 1999 concerning Foreign Relations which was later amended by Constitution Number 23 of 2014, and Constitution Number 24 of 2000 concerning International Treaties. Paradiplomacy is a relatively new concept but has been familiarly used or implemented by various local governments in Indonesia, so far paradiplomacy has been very successful in Indonesia as evidenced by the many international collaborations carried out by various regions, North Sumatra Province itself is no stranger to the concept of paradiplomacy seen from various foreign collaborations that have been carried out by the Medan City Government as the regional capital in the form of Sister Province/Sister City (Sister City, the role of the Provincial DPRD of North Sumatra (Sumut) as a legislative body that authorizes the approval of whether the cooperation can be carried out and reaps benefits by both parties or even harm.